2019
DOI: 10.1186/s13568-019-0894-2
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal potential of Streptomyces antibioticus strain M7 against Meloidogyne incognita

Abstract: Meloidogyne spp. are microscopic, obligatory endoparasites with worldwide distribution which cause severe damage to agricultural crops. The present study revealed the nematicidal activity of Streptomyces antibioticus strain M7 against Meloidogyne incognita. The culture supernatant of the isolate caused 100% J2 mortality after 24 h and inhibited egg hatching (only 3%). In addition, the nematicidal activity of actinomycins V, X2 and D purified from strain M7 was also checked. In vitro studies displayed 97.0–99.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Our study also revealed inclined levels of photosynthetic pigments in S. hydrogenans treated S. lycoperscum seedlings infested with M. incognita . Our findings are supported from the previous studies conducted by Sharma, et al [ 18 ] in tomato plants. They observed that plants treated with S. antibioticus strain M7 showed an enhancement in the levels of pigments due to triggered photosynthetic activities of plants.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study also revealed inclined levels of photosynthetic pigments in S. hydrogenans treated S. lycoperscum seedlings infested with M. incognita . Our findings are supported from the previous studies conducted by Sharma, et al [ 18 ] in tomato plants. They observed that plants treated with S. antibioticus strain M7 showed an enhancement in the levels of pigments due to triggered photosynthetic activities of plants.…”
Section: Discussionsupporting
confidence: 93%
“…This decline in plant pigments is mainly because of the inhibition of crucial enzymes required in the Violoxanthin pathway, this in turn impairs the stability of the photosynthetic apparatus [ 59 ]. Likewise, Sharma, et al [ 18 ] reported lowered or disrupted photosynthetic pigments in tomato plants subjected to nematode infections. Reduction in the plant pigments are attributed to the formation of galls over root surfaces, leading to disrupted water transportation and chlorophyll a and b levels [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nematodes are indeed endowed with high sensitivity to volatiles for their navigation in soil (Rasmann et al 2012a;Rengarajan & Hallem 2016). Previous studies have shown that volatiles from soil or root-associated microorganisms can affect nematode development and behaviour (Wuyts et al 2006;Turlings et al 2012;Cheng et al 2017;Sharma et al 2019;Wolfgang et al 2019). For example, volatiles emitted by some F. oxysporum strains negatively affect egg hatching of the root-knot nematode Meloidogyne incognita (Terra et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that volatiles from roots or soil microorganisms can affect nematode development and behaviour (Wuyts et al, 2006;Turlings et al, 2012;Cheng et al, 2017;Sharma et al, 2019;Wolfgang et al, 2019). For example, volatiles emitted by some F. oxysporum strains negatively affect egg hatching of the root-knot nematode Meloidogyne incognita (Terra et al, 2018).…”
Section: F Oxysporummentioning
confidence: 99%